2021
DOI: 10.30993/tifbr.v15i2.283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of The Board of Director's Characteristic On Islamic Bank's Financial Soundness

Abstract: The aims of this study is to diagnose the Board of Director’s characteristics and its impact on the financial soundness of Islamic banks. Regression analysis are applied to test the effect of the Board of Director's characteristics on the financial soundness of Islamic banking, employing a panel data composed of 67 Islamic banks during the period 2005-2014. The level of Islamic bank soundness is individually using the Z-score indicator. To verify the robustness of results, we use other dependent variables (CAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Yet, we also have evidence that large SSB would not be much effective to monitor the risk-taking behavior of management (AlAbbad et al, 2019). In contrast, some of the previous studies have found a negative relationship of Shari'ah board size with, at least, some measures of risks (AlAbbad et al, 2019;Safiullah and Shamsuddin, 2018;Fakhrunnas and Ramly, 2016):…”
Section: Corporate Governance and Risk Managementmentioning
confidence: 69%
See 1 more Smart Citation
“…Yet, we also have evidence that large SSB would not be much effective to monitor the risk-taking behavior of management (AlAbbad et al, 2019). In contrast, some of the previous studies have found a negative relationship of Shari'ah board size with, at least, some measures of risks (AlAbbad et al, 2019;Safiullah and Shamsuddin, 2018;Fakhrunnas and Ramly, 2016):…”
Section: Corporate Governance and Risk Managementmentioning
confidence: 69%
“…They can also influence the risk-taking practices of IFIs (Safiullah and Shamsuddin, 2018). On the other hand, Shari'ah board may also confine aggressive financings and investments and as a result, it lowers risk taking in the institutions (Fakhrunnas and Ramly, 2016). Furthermore, it is well evident that Shari'ah board has a significant, positive relationship with the performance of Islamic banks (Nawaz et al, 2021;Virk et al, 2022).…”
Section: Corporate Governance and Risk Managementmentioning
confidence: 99%